Competency-based Assessment Tools for Regional Anaesthesia: A Narrative Review. Issue 3 (September 2018) - Chuan, A.; Wan, A.S.; Royse, C.F.; Forrest, K.
Abstract : ( Br J Anaesth . 2018;120:264–273) Assessment tools play a critical role in the evaluation of trainee performance in competency-based postgraduate medical education programs. Consequently, the authors of the present narrative appraised published regional anesthesia assessment tools and addressed the type and purpose of current tools, relevant psychometric properties, implications for clinical adoption, and priorities in research.